(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
The diversity and species richness of insects were studied at the palm grove of El Ghrous. The insects were collected using two types of traps: Barber and Aerial. Forty-four insect species were inventoried. This inventory shows a predominance of Order Coleoptera with 6 families, 13 species and 241 individuals, followed by Hemiptera with 5 families, 7 species and 111 individuals, and Orthoptera with 2 families, 7 species and 54 individuals. J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(1): 85-94